Decision-making models and support systems for supply chain risk: Literature mapping and future research agenda - Marcus Vinicius Carvalho Fagundes; Eduardo Oliveira Teles; Silvio Alexandre Beisl Vieira de Melo; Francisco Gaudêncio Mendonça Freires (European Research on Management and Business Economics (ERMBE), 2020)
Supply chain disruptions have serious consequences for society and this has made supply chain risk management (SCRM) an attractive area for researchers and managers. In this paper, we use an objective literature mapping approach to identify, classify, and analyze decision-making models and support systems for SCRM, providing an agenda for future research. Through bibliometric networks of articles published in the Scopus database, we analyze the most influential decision-making models and support systems for SCRM, evaluate the main areas of current research, and provide insights for future research in this field. The main results are the following: we found that the identity of the area is structured in three groups of risk decision support models: (i) quantitative multicriteria decision models, (ii) stochastic decision-making models, and (iii) computational simulation/optimization models. We mapped six current research clusters: (i) conceptual and qualitative risk models, (ii) upstream supply chain risk models, (iii) downstream supply chain risk models, (iv) supply chain sustainability risk models, (v) stochastic and multicriteria decision risk models, and (vi) emerging techniques risk models. We identified seven future research clusters, with insights from further studies for: (i) tools to operate SCRM data, (ii) validation of risk models, (iii) computational improvement for data analysis, (iv) multi-level and multi-period supply chains, (v) agrifood risks, (vi) energy risks and (vii) sustainability risks. Finally, the future research agenda should prioritize SCRM's holistic vision, the relationship between Big Data, Industry 4.0 and SCRM, as well as emerging social and environmental risks.
Keywords: C500; C610; C630; M110; 650; bibliometrics; multicriteria decision; risk model; stochastic and computational model